Cement blocks adding stipa ichu fibers, in Mazocruz, Puno region - Huaricallo Vilca, Yvan (2023)
In the high Andean areas of southern Peru, extreme poverty is common, being susceptible to low temperatures in rural homes. Therefore, the manufacture of cement blocks is proposed by adding Ichu stipe fibers (Fibrocement) in the district of Santa Rosa-Mazo Cruz-Puno.Cement blocks were made by adding stipa ichu fibers, where the characteristics of stipa Ichu were evaluated, using physical and mechanical tests, the results obtained from the blocks were: Dimensional variation: maximum 0.19% in length, 0.68% in width and 0.39% high; Warpage: face 1 average of 1.17mm and face 2 average of 1.15mm; Absorption: 36.66% at 24 hours; Compression resistance: 61.62 kg/cm2 and Flexion: 11.23 kg/cm2.